PENENTUAN HARGA POKOK PENJUALAN SUTERA PADA PENGRAJIN SUTERA KAMPUNG SABBETA - Abidin, Dedy; Azis, Siti Nafisah; Mide, Nuraisyah Zain (Jurusan Akuntansi Politeknik Negeri Sriwijaya Palembang, 2023)
The ultimate goal of this activity is to provide good knowledge in the form of training on determining the cost of goods sold of silk, which is easily understood by silk craftsmen in Sabbeta's village. Currently, partners face several problems, especially regarding their knowledge in determining whether the business they run has bright prospects and sustainable profits now and in the future because they sell their production using estimates alone without doing professional calculations in determining sales prices.This activity was carried out in the form of training using lectures, questions and answers, exercises, feedback, and mentoring for the silk artisan community in Sabbeta village. This activity is located in Pising village, Donri-Donri sub-district, Soppeng Regency, South Sulawesi, which is about 140–150 km from the Ujung Pandang State Polytechnic campus.This activity has transferred new knowledge and skills to natural silk craftsmen in determining the cost of goods sold in silk production so as to produce maximum profits at competitive prices while still having purchasing power from consumers. Materials provided to partners include: first, identification of production costs; second, determination of the cost of goods produced; third, determination of the cost of goods sold; and fourth, calculation of operating profit.Keywords: Cost of Goods Sold, Operating Profit, Cost of Goods Produced